TINJAUAN ARSITEKTUR SEMIOTIKA MASJID RAMLIE MUSOFA - Mustawa, Bagas; Muktiono, Ayub (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2021)
Semiotics in architecture is a sign or symbol that aims to provide information to observers throughcertain forms. Thus, the process of interpreting a building that the architect wants to convey canbe lived by each individual building user. The meaning of an architectural object is not only limitedto the shape or appearance but is expected to be able to interpret the essential things hidden in aform that can be identified through in-depth observation.One of the places of worship, the mosque is a building that is very rich in meaning or message,because it has deep meaning for the beliefs of the people and their followers. The mosque is oneof the architectural works that composes beauty or aesthetic values with (spiritual) beliefs. This isreflected in the form, layout, and architectural elements of the building